Observations on the Evolution of the Melanocortin Receptor Gene Family: Distinctive Features of the Melanocortin-2 Receptor - Dores, Robert M. (Frontiers in Neuroscience, 2013)
The melanocortin receptors are a gene family in the rhodopsin class of G protein-coupled receptors. Based on the analysis of several metazoan genome databases it appears that the melanocortin receptors are only found in chordates. The presence of five genes in the family (i.e., MC1R, MC2R, MC3R, MC4R, MC5R) in representatives of the tetrapods indicates that the gene family is the result of two genome duplication events and one local gene duplication event during the evolution of the chordates. The melanocortin receptors are activated by melanocortin ligands (i.e., ACTH, α-MSH, β-MSH, γ-MSH, δ-MSH) which are all derived from the polypeptide hormone/neuropeptide precursor, POMC, and as a result the functional evolution of the melanocortin receptors is intimately associated with the co-evolution of POMC endocrine and neuronal circuits. This review will consider the origin of the melanocortin receptors, and discuss the evolutionary relationship between MC2R, MC5R, and MC4R. In addition, this review will analyze the functional evolution of the mc2r gene in light of the co-evolution of the MRAP (Melanocortin-2 Receptor Accessory Protein) gene family.